Solve this: t-(3t-1)=t-4 Please show it step by step

Question

Solve this: t-(3t-1)=t-4 Please show it step by step

in progress 0
Ariana 2 months 2021-10-10T13:42:14+00:00 2 Answers 0 views 0

Answers ( )

    0
    2021-10-10T13:43:17+00:00

    Answer:

    ANSWER

    t – (3t – 1) = t – 4

    t – 3t + 1 = t – 4

    -2t -t = -4 – 1

    -3t = -5

    t = 5/3

    Step-by-step explanation:

    0
    2021-10-10T13:44:03+00:00

    Answer:

    ∴ t = 5/3

    Step-by-step explanation:

    t- (3t-1) = t-4

    or, t – 3t + 1 = t-4

    or, -2t + 1 = t – 4

    or, 1 + 4 = t + 2t

    or, 5 = 3t

    ∴ t = 5/3

Leave an answer

Browse
Browse

18:9+8+9*3-7:3-1*13 = ? ( )